Humanitarian Mission in Pediatric Cardiothoracic Surgery: A Recipient's Perspective - Mohd Zain, Mohd Rizal; Shamsuddin, Ahmad Mahir; Mamat, Ahmad Zuhdi; Mokhtar, Ariffin Marzuki; Ali, Saedah; Chen, Yen Chuan; Corno, Antonio F. (Frontiers in Pediatrics, 2019)
Introduction : Paediatric Cardiac Surgical Mission programmes are deemed as common practice, especially in developing nations funded by international nongovernmental organizations (NGOs). This article presents and discusses the results and strategies implemented by this partnership, aiming at achieving the autonomy of the local centre by this collaboration. Materials and Methods : A retrospective review was conducted on patients with congenital heart disease who underwent surgical intervention from the beginning of NGOs collaboration (September 2015) until November 2018 in an existing cardiac centre. In between those visits, any congenital heart disease patient with Risk Adjustment Congenital Heart Surgery (RACHS)-1 Category 1-3 would be discussed in a local multi-disciplinary meeting with regards to the feasibility of the surgery being performed by the local members. Results: A total of 60 operations have been performed during the trips. Throughout the visit, 46% (28) of the operations were performed by the local surgeon, with or without assistance from the visiting surgeon. Between September 2015 until November 2018, 27 cases were also performed by local team independently. For the 27 cases performed by local team independently, the median age of patient was 42 days (ranging from 14 days to 20 years old), with median body weight of 3.2kg (ranging from 2.8-64kg). Conclusion : Humanitarian paediatric cardiac surgical missions are safe to be done for the population in need. In order to achieve autonomy, continuous efforts by both teams are crucial as the cooperation by the two parties ensures that the objectives are achieved.